2019
DOI: 10.1523/jneurosci.1064-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of TRPV1 S801 Contributes to Modality-Specific Hyperalgesia in Mice

Abstract: Transient receptor potential vanilloid subtype 1 (TRPV1) is a nonselective cationic channel activated by painful stimuli such as capsaicin and noxious heat, and enriched in sensory neurons of the pain pathway. During inflammation, chemical mediators activate protein kinases (such as PKC) that phosphorylate TRPV1 and thereby enhance its function, with consequent increases in nociceptor sensitization. However, the causal relationships between TRPV1 phosphorylation and pathological pain remain unexplored. To dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…NMDA increases PKC-dependent phosphorylation of TRPV1 serine 800 residue (TRPV1 S800) in dissociated trigeminal neurons, suggesting that TRPV1 S800 phosphorylation is a convergent pathway in the glutamate-induced regulation of TRPV1 (Lee, Chung, and Ro 2012). In a mouse line in which TRPV1 S801, an orthologue residue of rat TRPV1 S800, is mutated into alanine to prevent phosphorylation, mouse grimace scale (MGS) following masseteric CFA injection is attenuated as compared with wild-type mice, suggesting that TRPV1 S801 phosphorylation-dependent mechanisms contribute to CFA-induced spontaneous pain (Joseph et al 2019).…”
Section: Primary Afferents For Acute and Chronic Craniofacial Muscle mentioning
confidence: 99%
See 1 more Smart Citation
“…NMDA increases PKC-dependent phosphorylation of TRPV1 serine 800 residue (TRPV1 S800) in dissociated trigeminal neurons, suggesting that TRPV1 S800 phosphorylation is a convergent pathway in the glutamate-induced regulation of TRPV1 (Lee, Chung, and Ro 2012). In a mouse line in which TRPV1 S801, an orthologue residue of rat TRPV1 S800, is mutated into alanine to prevent phosphorylation, mouse grimace scale (MGS) following masseteric CFA injection is attenuated as compared with wild-type mice, suggesting that TRPV1 S801 phosphorylation-dependent mechanisms contribute to CFA-induced spontaneous pain (Joseph et al 2019).…”
Section: Primary Afferents For Acute and Chronic Craniofacial Muscle mentioning
confidence: 99%
“…Nonpeptidergic masseter afferents that bind isolectin B4 (IB4) are rare (5%; Ambalavanar et al 2003). In TG, TRPV1 is predominantly expressed in peptidergic afferents (Joseph et al 2019), and approximately 25% of masseter afferents express TRPV1 (Ro et al 2009). Recent studies have offered convincing evidence for the TRPV1 contribution to craniofacial muscle pain.…”
Section: Glutamate Receptor and Trp Channel Mechanisms In Peptidergicmentioning
confidence: 99%
“…The higher activities of corneal cold-sensitive nerves in previous reports would be maintained by endogenous TRPV1 ligands generated by ocular inflammation since perfusion of the TRPV1 antagonist in the present study had no significant effect on ongoing activities in cold-sensitive nerves (data not shown). Joseph et al (2019) reported that the phosphorylation of TRPV1 at S801 sensitizes the TRPV1-mediated current response in sensory neurons and potentiates pain behavior, which is involved in the generation of spontaneous pain in masseter inflammation. Therefore, TRPV1 phosphorylation may contribute to the sensitization of the TRPV1-mediated response under chronic tear deficiency in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Joseph et al ( 2019 ) reported that the phosphorylation of TRPV1 at S801 sensitizes the TRPV1-mediated current response in sensory neurons and potentiates pain behavior, which is involved in the generation of spontaneous pain in masseter inflammation. Therefore, TRPV1 phosphorylation may contribute to the sensitization of the TRPV1-mediated response under chronic tear deficiency in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Masseter injection of TRPV1 antagonist further decreases spontaneous pain in both knock-in and wild-type (WT) genotypes, and the extent of inhibition is greater in WT than knock-in, suggesting that CFA-induced spontaneous pain is mediated by TRPV1 S801 phosphorylationdependent and independent mechanisms. 89 Masseter hyperalgesia induced by CFA or the injection of NMDA is also attenuated by TRPA1 inhibitor, suggesting interaction of NMDA receptor and TRPA1 in masseter afferents. 63 Although mechanisms underlying glutamate receptor and TRPA1 are not known, and need to be determined, it is noteworthy that TRPA1 phosphorylation also contributes to nociception.…”
Section: Activation Of Glutamate Receptors Regulates Trp Channel Signmentioning
confidence: 94%